A Rare Case of Multifocal Papillary Thyroid Cancer in Bilateral Thyroid Cysts - Anupama Roy Chowdhury; Jack Kian Ch’ng; Choon Chieh Tan (Case Reports in Medicine)
Papillary thyroid cancer (PTC) can present as a thyroid cyst. In its more aggressive form, PTC may be multifocal in nature and is associated with a poorer prognosis. In patients whom PTC is diagnosed incidentally after a diagnostic lobectomy, the decision whether to offer completion thyroidectomy is sometimes challenging to make if such patients fall in the ‘low-to-intermediate’ risk category. We present a case of a 55-year-old lady who had a predominantly cystic left thyroid nodule with no suspicious features on ultrasound as well as 2 subcentimetre simple right-sided cysts. She subsequently underwent left hemithyroidectomy, and this reported a T2 PTC in the thyroid cyst. This was followed by completion thyroidectomy which yielded the surprising finding of PTC in the two tiny right sided cysts. This case highlights the need for vigilance in managing patients with thyroid cysts even though thyroid ultrasound scan did not reveal any overt suspicious features.